Textos de divulgação científica no ensino de física moderna na escola média - Chaves, Taniamara Vizzotto (2002)
This work has as objective to evaluate the possibilities and perspectives for modern and contemporary physics introduction in the High School using as didactic resource texts of scientific popularization. The mentioned authors defend the possibility to develop in class room a physics that exists in the extraschool context, be through the apparatuses or technological inventions or through the Social Communication Means, among the ones are Newspapers and Magazines. The information were collected starting from the joint work with a group of teachers, in have been continuous formation, operating in the discipline of Physics of High Teaching. Several instruments of collection of information have been used, among them the Newspapers of the teachers' Pedagogic Practice, to audio recording of the teachers' spontaneous reports, besides the video-recording of the classes. The analysis of the information collected in relation to structuring, implementation and evaluation of the accomplished activities, revealed some limitations on the part of the teachers in the direction of dominating modern physics concepts and approached contemporary, to introduce strategies differentiated for the use of the popularization texts and finally, in the elaboration writing of the Newspapers of the Pedagogic Practice. Looking for to find and to overcome the reasons of such limitations, we accomplished an interview semi-structured with the teachers to investigate the possible relationships among the history of reading of these and the understanding and use that the same ones do of the texts of scientific popularization. The analysis of these interviews allowed us more to know a little more of the reality or history of the teachers' reading. In this sense, we could notice that the teachers are eventual readers of whole material type and of diversified subjects, but they center its attentions in related subjects the Science and technology and the physics that are teaching in the school. Besides, the largest reading frequency is in the Newspapers and in the Didactic Books. The Magazines of Scientific Popularization are generally consulted and reads its periodicity and interest accordingly for some specific subject, or to be introduced in the pedagogic didactic plannings elaborated in the ambit of GTPF. These results allowed us to conclude that the limitations found by the teachers can be related its little reading practice. These limitations are especially proceeding of the initial formation in Physics where the reading practices are not a constant and it has its continuity during the exercise of the profession for the work e specially for the conditions that one that the teachers are exposed.